PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI SATU ATAP 2 MERANGIN - Herli Korneles; Hidayati Rais; Ferinaldi (Hiradika | Hira Institute, 2025)
This research is based on the low mathematics learning outcomes of students in mathematics subjects on the subject of quadrilaterals and triangles. The low mathematics learning outcomes of students are due to the lack of precision in the learning model used so that students are less motivated to learn. This research aims to improve mathematics learning outcomes through the application of the Problem Based Learning learning model for grade VII students of SMPN Satu Atap 2 Merangin for the 2023/2024 school year. This type of research design is a class action research (PTK) which is carried out in grade VII of SMPN Satu Atap 2 Merangin for the 2023/2024 school year. This research consists of three cycles, each cycle has three meetings, two material meetings and one test meeting. The research subjects of grade VII students for the 2023/2024 academic year are 14 students. The data collected using a learning outcome test in the form of 5 essay questions and observation of student and teacher activities. The results of this study showed that the average score of the student mathematics learning outcome test increased in the first cycle by 59.86, increased in the second cycle to 66.71 and increased in the third cycle to 75.93. The results of observation data are known that the average percentage of student learning activities in cycle I is 57.14%, in cycle II to 73.48% and in cycle III to 83.45%, gradually increasing in cycle I to cycle II has increased by 16.34% and from cycle II to cycle III has increased by 9.97%. From these results, it can be concluded that the Problem Based Learning model can improve the mathematics learning outcomes of grade VII students of SMPN Satu Atap 2 Merangin for the 2023/2024 school year.